2009
DOI: 10.1007/s10464-009-9252-x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Engagement and Barriers to Participation in a Community‐Based Preventive Intervention

Abstract: This study examined parent characteristics and barriers to participation in a community-based preventive intervention with a sample of 201 parents from low-income and predominantly ethnic minority backgrounds. Person-centered analyses revealed five subgroups of parents who demonstrated variability in their parent characteristics, which included psychological resources and level of parental involvement in education. Group membership was associated with differences in school involvement and use of the psychoeduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 40 publications
6
52
0
Order By: Relevance
“…Despite these limitations, and past research has shown that individuals of lower socioeconomic status experience more barriers to participation and are less likely to enroll in interventions. 22 Our findings suggest that sociocultural recruitment mediums may increase the diversity and generalizability of socioeconomic backgrounds among participants, but further research is needed to replicate these findings.…”
Section: Culturally Relevant Recruitment -Huffman Et Almentioning
confidence: 69%
“…Despite these limitations, and past research has shown that individuals of lower socioeconomic status experience more barriers to participation and are less likely to enroll in interventions. 22 Our findings suggest that sociocultural recruitment mediums may increase the diversity and generalizability of socioeconomic backgrounds among participants, but further research is needed to replicate these findings.…”
Section: Culturally Relevant Recruitment -Huffman Et Almentioning
confidence: 69%
“…The fact that a person is obese and appreciates that he or she has associated lifestyle difficulties related to his or her obesity may not predict whether a person will choose to exercise or choose an alternate diet (Mastellos, Gunn, Felix, Car, & Majeed, 2014). In the parenting domain, in addition to perceived parenting skills and severity of child behaviors, factors that may also influence decision making could include (a) parent characteristics (e.g., mental health, parental competencies, parental attributions and cognitions), (b) social challenges (e.g., socioeconomic status), (c) family factors (e.g., supportive co-parent), and (d) cultural practices and other domains that impact health decision making (Mendez et al, 2009;Nock & Ferriter, 2005;Williford, Graves, Shelton, & Woods, 2009). Including some of these variables in largerscale studies to determine a broader scope of factors that influence parents' decisions to participate in treatment may clarify distinctions between the almost ready and ready groups identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although widely used, these interventions are not satisfactory for many parents (Mendez, Carpenter, LaForett, & Cohen, 2009;Miller & Prinz, 2003). A large proportion of parents choose not to participate in these treatments, and those who do show concerning rates of dropout (Frankel & Simmons, 1992;Kazdin & Wassell, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their studies have implications for understanding the role that technology can play in extending the reach of evidence-based parenting programs, particularly among minority groups that are disproportionately exposed to poverty and corresponding risk factors that can increase children's vulnerability to negative outcomes (Lopez and Velasco 2011;McLoyd 2011;Schickedanz et al 2015). Internet-delivered interventions have the potential to address logistical barriers such as transportation, childcare, and lack of time, which are most commonly experienced by lowincome families (Mendez et al 2009). Children from lowincome families are at greatest risk for negative outcomes but their parents are also least likely to participate in preventive interventions; as such, research informing delivery modalities that might be effective in reaching this populations is valuable.…”
Section: Enhancing Intervention Participation Is a Translational Resementioning
confidence: 99%